-51=-4(8x+5)+7(x-8)

Simple and best practice solution for -51=-4(8x+5)+7(x-8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -51=-4(8x+5)+7(x-8) equation:


Simplifying
-51 = -4(8x + 5) + 7(x + -8)

Reorder the terms:
-51 = -4(5 + 8x) + 7(x + -8)
-51 = (5 * -4 + 8x * -4) + 7(x + -8)
-51 = (-20 + -32x) + 7(x + -8)

Reorder the terms:
-51 = -20 + -32x + 7(-8 + x)
-51 = -20 + -32x + (-8 * 7 + x * 7)
-51 = -20 + -32x + (-56 + 7x)

Reorder the terms:
-51 = -20 + -56 + -32x + 7x

Combine like terms: -20 + -56 = -76
-51 = -76 + -32x + 7x

Combine like terms: -32x + 7x = -25x
-51 = -76 + -25x

Solving
-51 = -76 + -25x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '25x' to each side of the equation.
-51 + 25x = -76 + -25x + 25x

Combine like terms: -25x + 25x = 0
-51 + 25x = -76 + 0
-51 + 25x = -76

Add '51' to each side of the equation.
-51 + 51 + 25x = -76 + 51

Combine like terms: -51 + 51 = 0
0 + 25x = -76 + 51
25x = -76 + 51

Combine like terms: -76 + 51 = -25
25x = -25

Divide each side by '25'.
x = -1

Simplifying
x = -1

See similar equations:

| -3x+2(2x+4)=-(4x+6)-6 | | 4X-1(3X+11)=-11 | | (a+b)*2= | | 0=6x^2-9x | | 4(2y-13)-9(y-3)+2(3y-10)=0 | | 2(-2y+1)=4y+18 | | n(n+1)+(n+2)=258 | | 0=x^2+9 | | 4(x-2)=2x-7+4x | | Y=2x^2+5x-1 | | -6(n+7)-5(6+3n)=-51 | | 8x+6m=26 | | 40-2x*e^2x=0 | | 0=2x^2+25x+5000 | | 4(x+9)-10x=-6(x+1)+10 | | 0=2x^2+25+5000 | | 12y-40=y-42 | | 5s-1=-11 | | -19=-3g+2 | | 9-3x=5(x-3) | | G^2-2g-80=0 | | 11(s+169)-307=56 | | 3=-2(b-2)-5(-b+2) | | 4m+4m=4m | | .4(3x+4)-10=6 | | 2(4+3)-6(0)= | | -27(k+776)=729 | | (6-k)+4=(9+k)-21 | | 12x-4=12x-2 | | 6w=5w-3 | | 7b-10b=-18 | | -5x^2+3=97 |

Equations solver categories